Ultrasound in paediatric anaesthesia – A comprehensive review. (May 2021) - Haroon-Mowahed, Yumna; Cheen Ng, Su; Barnett, Sarah; West, Simeon
The use of ultrasound is becoming more widespread in anaesthesia. In this review, we discuss the use of ultrasound in various aspects of paediatric anaesthesia and how it can be used to assist diagnostic and therapeutic interventions and the evidence available. We explore the use of ultrasound as an adjunct for regional anaesthesia, vascular access, airway management, bedside cardiac, pulmonary and abdominal imaging and intracranial pressure monitoring.